2013
DOI: 10.5489/cuaj.1173
|View full text |Cite
|
Sign up to set email alerts
|

NMP22 is predictive of recurrence in high-risk superficial bladder cancer patients

Abstract: Introduction: The nuclear matrix protein 22 (NMP22) assay has been shown to have greater sensitivity for the diagnosis and detection of recurrent urothelial carcinoma of the bladder (UCB) over that of traditional urine cytology. We assessed the use of NMP22 to predict which high-risk superficial UCB patients will have recurrence, progression or disease-related death; we compared these results to standard urine cytology. Methods:One hundred consecutive patients with high-risk superficial UCB were enrolled. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Although, as recurrence‐associated factors, there were no associations between the pretreatment values of NMP22 and recurrence values . Most recent studies reported good negative predictive values (90–93%) indicating that a high proportion of individuals testing negative do not have bladder cancer . Another concern is serial measurements of NMP22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, as recurrence‐associated factors, there were no associations between the pretreatment values of NMP22 and recurrence values . Most recent studies reported good negative predictive values (90–93%) indicating that a high proportion of individuals testing negative do not have bladder cancer . Another concern is serial measurements of NMP22.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Lau et al the data suggested that patients with high‐risk superficial UC who are NMP22 positive with negative cystoscopies are even more likely to recur than patients who are NMP22 negative. Thus, this might also identify a selected group of patients that should undergo intravesical therapy with maintenance …”
Section: Discussionmentioning
confidence: 99%
“…Based on accurate and early diagnosis of a disease, suitable treatment choices can be made. The US Food and Drug Administration (FDA) has approved bladder tumor antigen (BTA) and nuclear matrix protein-22 (NMP-22) [53] as diagnostic markers for bladder cancers based on urine analysis. De Petris et al [54] confirmed CYFRA21-1 as a diagnostic marker for lung cancer.…”
Section: Biomarkersmentioning
confidence: 99%
“…Lau et al assessed the use of NMP22 to predict which high-risk superficial UCB (urothelial carcinoma of the bladder) patients would have a recurrence, progression or diseaserelated death. According to their finding, they deem that the NMP22 assay appears to have predictive value for future tumour recurrences (Lau et al, 2009). Kundal et al assess the clinical utility of NMP22 Bladder Check Test and compare it with voided urine cytology and cystoscopy in early detection of bladder cancer.…”
Section: Urinary Markers Of Bladder Cancer Nmp22mentioning
confidence: 99%